Factors Affecting the Interest of Prospective Hajj Pilgrims Choosing Arafah Savings at PT. Bank Muamalat Indonesia Tbk KCU Padangsidimpuan - afni lestari; darwis harahap; sry lestari; syuaib nasution (Journal Of Sharia Banking, 2020)
This research is motivated by the lack of interest of prospective pilgrims in choosing Hajj Arafah savings at PT. Bank Muamalat Indonesia Tbk KCU Padangsidimpuan, the data obtained fluctuated. The purpose of this study was to determine the effect of promotion, service, and product simultaneously on customer interest in choosing Hajj Arafah savings savings at Bank Muamalat Indonesia Tbk KCU Padangsidimpuan. This research is a quantitative research, the data source used is primary data. The data collection technique used is a questionnaire, with a sample of 92 respondents and the sample measurement technique is the Slovin formula. The analysis used is validity test and reliability test and classical assumption test. Multiple linear regression analysis, hypothesis testing and determination coefficient test R2. The results of this study simultaneously promotion, service, and product simultaneously influence the interest of prospective pilgrims to choose Arafah savings at PT. Bank Muamalat Indonesia Tbk KCU Padangsidimpuan.